2012
DOI: 10.2220/biomedres.33.363
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor induces mRNA expression of pro-inflammatory factors in the uterine cervix of mice

Abstract: Inflammation is believed to play a role in uterine cervical remodeling and infection-induced preterm labor. One of the distinct features of remodeling uterine cervix is presence of prominent vascular events, such as angiogenesis, vasodilation, and vascular permeability. Although the functional significance of these features is not yet clear, we know that in most tissue types, vascular remodeling is intricately intertwined with inflammation. Since vascular endothelial growth factor (VEGF) is the major architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
(55 reference statements)
1
19
0
1
Order By: Relevance
“…We recently demonstrated that exogenous VEGF administered vaginally (intraluminally) induces an inflammatory response by upregulating mRNA expression of classical pro-inflammatory factors, including TNFa, IL6, and COX II, implying that VEGF likely plays a role in the inflammatory response of uterine cervical epithelial cells during pathogenic invasions (Nguyen et al 2012). These observations are also consistent with our earlier DNA microarray studies that observed a 4.70-fold decrease in genes associated with immune response and decrease in expression of an array of chemokine, interleukins, and LPS binding protein, when VEGF actions were blocked in the cervix of pregnant rats by VEGF inhibitor .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that exogenous VEGF administered vaginally (intraluminally) induces an inflammatory response by upregulating mRNA expression of classical pro-inflammatory factors, including TNFa, IL6, and COX II, implying that VEGF likely plays a role in the inflammatory response of uterine cervical epithelial cells during pathogenic invasions (Nguyen et al 2012). These observations are also consistent with our earlier DNA microarray studies that observed a 4.70-fold decrease in genes associated with immune response and decrease in expression of an array of chemokine, interleukins, and LPS binding protein, when VEGF actions were blocked in the cervix of pregnant rats by VEGF inhibitor .…”
Section: Discussionmentioning
confidence: 99%
“…Animals with normal uterine size 7 days after ovariectomy were eliminated from the study. Appropriate treatments were administered by injecting either vehicle only (negative control: 0.1 M PBS mixed with saturated (25%) pluronic gel and kept in liquid form under ice) or VEGF agonist (mouse recombinant VEGF 164 protein (Calbiochem, La Jolla, CA, USA)) to nonpregnant ovariectomized mice (nZ3/treatment group), following dosage, frequency, and route optimization, as described below and previously (Nguyen et al 2012). Some mice were also treated with VEGF inhibitor (PTK 787/ZK22584; generously provided by Novartis Pharma AG):…”
Section: Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations